ENHANCING IPE FACILITATOR CAPACITY: A TRAINING PROGRAM ON UTILIZING THE RESPECT QUESTIONNAIRE TO EVALUATE INTERPROFESSIONAL REFLECTION ABILITY - Ameli Dwi Fitri; Anggelia Puspasari; Citra Maharani; Rina Nofri Enis; Erny Kusdiyah; Wahyu Indah Dewi Aurora; Nyimas Natasha Ayu Shafira; Herlambang (Universitas Jambi, 2025)
ABSTRACT Interprofessional Education (IPE) is a mandated learning process to prepare